Youth soccer coaches' profile, experience and teaching methods in the province of Huelva - José Robles Rodríguez; Francisco Javier Giménez Fuentes-Guerra; Manuel Tomás Abad Robles; José María Rodríguez López (FEADEF, 2011)
The coach is the key in sport training with young sportsmen; it became one of the most influential powers in the right development of boys and girls (Jones, 1992). This study tried to show the profile and the experience of football coaches in the province of Huelva, as well as the teaching methods used. 79 football coaches of the province of Huelva were analysed with the help of a survey. The data showed that the profile of a football coach for children of the province of Huelva corresponded to the following: male, between 21 and 30 years, graduated secondary school, B.U.P./C.O.U., who is playing or played football, and had been training at the youth football between 0 and 5 years. Outstanding within the results was that people with a lower level of football qualification, had less experience in the field of training a football team. Furthermore, about half of the coaches used direct teaching methods. It would be suitable to carry out studies about coaches of young football players. Through observation studies our collected data could be verified